Mycobacterium abscessus subsp. abscessus Is Capable of Degrading Pseudomonas aeruginosa Quinolone Signals - Birmes, Franziska S.; Wolf, Timo; Kohl, Thomas A.; Rüger, Kai; Bange, Franz; Kalinowski, Jörn; Fetzner, Susanne (Frontiers in Microbiology, 2017)
Pseudomonas aeruginosa employs 2-heptyl-3-hydroxy-4(1H)-quinolone (the Pseudomonas quinolone signal, PQS) and 2-heptyl-4(1H)-quinolone (HHQ) as quorum sensing signal molecules, which contribute to a sophisticated regulatory network controlling the production of virulence factors and antimicrobials. We demonstrate that Mycobacterium abscessusT and clinical M. abscessus isolates are capable of degrading these alkylquinolone signals. Genome sequences of 50 clinical M. abscessus isolates indicated the presence of aqdRABC genes, contributing to fast degradation of HHQ and PQS, in M. abscessus subsp. abscessus strains, but not in M. abscessus subsp. bolletii and M. abscessus subsp. massiliense isolates. A subset of 18 M. a. subsp. abscessus isolates contained the same five single nucleotide polymorphisms (SNPs) compared to the aqd region of the type strain. Interestingly, representatives of these isolates showed faster PQS degradation kinetics than the M. abscessus type strain. One of the SNPs is located in the predicted promoter region of the aqdR gene encoding a putative transcriptional regulator, and two others lead to a variant of the AqdC protein termed AqdCII, which differs in two amino acids from AqdCI of the type strain. AqdC, the key enzyme of the degradation pathway, is a PQS dioxygenase catalyzing quinolone ring cleavage. While transcription of aqdR and aqdC is induced by PQS, transcript levels in a representative of the subset of 18 isolates were not significantly altered despite the detected SNP in the promoter region. However, purified recombinant AqdCII and AqdCI exhibit different kinetic properties, with approximate apparent Km values for PQS of 14 µM and 37µM, and kcat values of 61 s-1 and 98 s-1, respectively, which may (at least in part) account for the observed differences in PQS degradation rates of the strains. In co-culture experiments of P. aeruginosa PAO1 and M. abscessus, strains harboring the aqd genes reduced the PQS levels, whereas mycobacteria lacking the aqd gene cluster even boosted PQS production. The results suggest that the presence and expression of the aqd genes in M. abscessus lead to a competitive advantage against P. aeruginosa.